1990
DOI: 10.2307/3577738
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Radiofrequency Radiation on Chromosome Aberrations in CHO Cells and Its Interaction with DNA-Damaging Agents

Abstract: A limited number of contradictory reports have appeared in the literature about the ability of radiofrequency (rf) radiation to induce chromosome aberrations in different biological systems. The technical documentation associated with such reports is often absent or deficient. In addition, no information is available as to whether any additional genotoxic hazard would result from a simultaneous exposure of mammalian cells to rf radiation and a chemical which (by itself) induces chromosome aberrations. In the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(14 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…In addition, cell phone radiation can alter protooncogene activity (Ivaschuk et al, 1997;Goswami et al, 1999). However, a similar number of studies have failed to detect obvious clastogenic effects following microwave irradiation of isolated animal cells in vitro (Alam et al, 1978;Lloyd et al, 1984Lloyd et al, , 1986Wolff et al, 1985;Meltz et al, 1987Meltz et al, , 1989Meltz et al, , 1990Kerbacher et al, 1990;Maes et al, 1997Maes et al, , 2001. Thus, there is still no conclusive answer as to whether exposure to microwaves is clastogenic, i.e., whether they can direct or indirectly increase the frequency of chromosomal aberrations.…”
Section: Introductionmentioning
confidence: 86%
“…In addition, cell phone radiation can alter protooncogene activity (Ivaschuk et al, 1997;Goswami et al, 1999). However, a similar number of studies have failed to detect obvious clastogenic effects following microwave irradiation of isolated animal cells in vitro (Alam et al, 1978;Lloyd et al, 1984Lloyd et al, , 1986Wolff et al, 1985;Meltz et al, 1987Meltz et al, , 1989Meltz et al, , 1990Kerbacher et al, 1990;Maes et al, 1997Maes et al, , 2001. Thus, there is still no conclusive answer as to whether exposure to microwaves is clastogenic, i.e., whether they can direct or indirectly increase the frequency of chromosomal aberrations.…”
Section: Introductionmentioning
confidence: 86%
“…In vitro investigations of Kerbacher et al [1990] and Meltz et al [1990] on different cell systems provided evidence for a lack of direct genotoxic and mutagenic effects of continuous and pulsed microwaves at different power densities; furthermore, no synergistic effect was found between the applied field and Mitomycin-C, Adrianmycin, and Proflavin. Ciaravino et al [1991] also found no synergistic effect between moderate power radio frequency electromagnetic radiation and Adriamycin on cell cycle progression and sister chromatid exchanges.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these studies did not make any definite statements about genotoxic and co-genotoxic effects of RF-EMF, and stated that further research is needed [Li et al, 2001;Meltz, 2003;Verschaeve et al, 2006]. Temperature elevation due to high SAR levels is one of the most established putative mechanisms leading to genotoxic effects by RF radiation [Kerbacher et al, 1990], and most studies have shown genotoxic and cogenotoxic effects of RF radiation at high SAR values (>3 W/kg). In this study, the human lymphocytes placed in the MRI scan were only exposed to SAR values below 3 W/kg and the sample temperature was controlled.…”
Section: Discussionmentioning
confidence: 99%